Cives romani in marmoris arte periti: the Classical World and the Renewal of the Cloister Model in 13th century Rome - Roberta, Cerone (Actual Problems of Theory and History of Art, 2015)
An introduction of the cloister in Rome starts in the 12th century (Tre Fontane, S. Lorenzo fuori le mura, S. Cecilia in Trastevere), but it’s only in the 13th century that we find a systematic usage of the cloister as the main element in planning of old and new monastic foundations. In parallel with its spreading the typical Roman cloister, as it was codified during the 12th century, undergoes a radical change, partly due to the involvement of the different artists of Roman marmorarii families: Cosmati and Vassalletto. These sculptors considered themselves discendants of Classical Rome and, in the name of that heritage, they reinterpreted forms and motifs of architectural sculpture from Roman period through the reuse and the reworking of marbles taken from ancient monuments. This change started in the monastery of S. Scolastica in Subiaco near Rome under the aegis of pope Innocent III and then involved the main complexes of the Urbe.